The New Rural Social Pension Program in rural China: Participation and its correlates - Qiran Zhao; Stephan Brosig; Renfu Luo; Linxiu Zhang; Ai Yue; Scott Rozelle (China Agricultural Economic Review, 2016)
Purpose: The need for a universal rural pension system has been heightened by demographic changes in rural China, including the rapid aging of the nation's rural population and a dramatic decline in fertility. In response to these changes, China's Government introduced the New Rural Social Pension Program (NRSPP) in 2009, a voluntary and highly subsidized pension scheme. The purpose of this paper is to assess the participation of rural farmers in the NRSPP. Furthermore, the authors examine whether the NRSPP affects the labor supply of the elderly population in China. Design/methodology/approach: This paper uses household-level data from a sample of 2,020 households originating from a survey conducted by the authors in five provinces, 25 counties, and 101 villages in rural China. Using a probit model and conducting correlation analysis, the authors demonstrate the factors affecting the participation and the impact of NRSPP on labor supply of the rural elderly. Findings: The results show there are several factors that are correlated with participation, such as specific policy variant in force in the respective household's province, the size of the pension payout from government, the age of sample individuals, and the value of household durable assets. Specifically, different characteristics of NRSPP policy implementation increase participation in China's social pension program. The results suggest that the introduction of the NRSPP has not affected the labor supply of the rural elderly, in general, although it has reduced participation for the elderly who were in poor health. Originality/value: Several previous studies have covered the NRSPP. However, all previous studies were based on case studies or just focused on a small region, and for this reason the results cannot reflect the populations and heterogeneity of rural areas. Therefore, a data set with a large sample size is used in this paper to provide a new perspective to fully understand the participation of NRSPP and its impacts on rural households. This paper will make an update contribution to the literature in the area of pension programs in China.
Keywords: 330; China; rural; labor supply; participation behavior; New Rural Social Pension Program